Regulation of osteoblasts by alkaline phosphatase in ankylosing spondylitis. (11th November 2018) - Jo, Sungsin; Han, Jinil; Lee, Young L.; Yoon, Subin; Lee, Jaehyun; Wang, Sung E.; Kim, Tae‐Hwan
Abstract: Aim: Ankylosing spondylitis (AS) is characterized by excessive spinal ankylosis and bone formation. Alkaline phosphatase (ALP) activity is reported to be high in AS, but little is known about the molecular relationship between ALP and AS. The aims of this study were to investigate the relevance of ALP to AS and the role of ALP in the regulation of osteoblast differentiation in AS. Methods: High‐throughput data with accession numbers GSE73754 and GSE41038 were downloaded from the Gene Expression Omnibus. We retrospectively collected and compared the ALP levels of male patients with AS to those of sex‐ and age‐matched healthy controls (HC) and rheumatoid arthritis (RA) patients. Total serum ALP and ALP activity were measured in the AS and RA groups. ALP gene expression and intracellular ALP activity were analyzed in microarray data from primary diseases control (Ct) and AS‐bone‐derived cells (BdCs) and in vitro experiments. Furthermore, the effect of ALP inhibitor was examined in both primary Ct‐ and AS‐BdCs under osteoblast differentiation. Regulation of runt‐related transcription factor 2 (RUNX2) by ALP was also analyzed. Results: Alkaline phosphatase level was higher in AS compared with RA and HC and was associated with radiograph progression. ALP expression was also enriched in the bone tissue of AS patients. Furthermore, AS‐BdCs exhibited increasing ALP activity, leading to accelerated osteoblastic activity and differentiation. Intriguingly, inhibition of ALP reduced RUNX2 expression, a master transcriptional factor in osteoblasts, and differentiation status of both primary Ct‐ and AS‐BdCs. Treatment of ALP activator or inhibitor modulated RUNX2 protein level and RUNX2 regulated ALP promoter activity, indicating a reciprocal ALP‐RUNX2 positive feedback to regulate osteoblast differentiation. Conclusion: Alkaline phosphatase was highly expressed in AS patients, may be involved in the ankylosis of AS, and represents a possible therapeutic target for ankylosis.